Desempenho econômico-financeiro versus desempenho esportivo: um estudo comparativo entre clubes de futebol do Brasil e da Inglaterra - Almeida, Cássio Rodrigo da Costa (2021)
Football stands out worldwide as a phenomenon that goes beyond the sports sphere, considered an essential part in the sports industry, as well as for society. Over the years it turned into a billionaire business, mainly due to negotiations involving its players. However, this football expansion started to attract attention not only from fans, but from a specific audience, such as sponsors and investors. The clubs then began to structure a strong team, which achieved good sporting and financial performance, allowing for the collection of more resources. In view of this, the main objective of the research was to investigate the relationship between the economic and financial performance and the sporting performance of the main football clubs in Brazil and England from 2015 to 2019. The study is considered a data collection secondary, having a descriptive nature, with a statistical and documentary bias. As for the sample, it was defined based on two scenarios. Scenario one lists the Brazilian clubs, which were selected following the participation criteria of the teams that remained in the highest division of the Brazilian Championship in the last five seasons, from 2015 to 2019. Scenario two, on the other hand, lists the English clubs, which were selected following the criteria for the participation of teams that remained in the highest division of the Premier League, in the period covering the last five seasons, corresponding to the period from 2015/2016 to 2019/2020. Altogether, eleven Brazilian and thirteen English clubs were selected. To construct the financial factor, data were extracted from the Balance Sheet and Income Statement for the year, based on seven economic-financial indicators. The independent variables were also defined, adopting the CBF Club Ranking for Brazilian clubs and the general classification of the Premier League first division for the English. Then, the control variables were defined, these being the population, transmission channel, own stadium, number of games and victories for Brazilians and spectators per stadium, transmission channel, own stadium, number of games and victories for the English. Related to the data analysis process, the econometric technique of regression with panel data was used, applied with the Gretl software, in addition to the use of the Bayesian Network technique, to discuss the relationship between financial performance and sports performance. The results showed that the liquidity indicators had averages lower than what is considered ideal for the indicator. In the case of Brazilians, they showed a very low payment capacity, putting their finances at risk. For the English, such values were considered low, but still higher than for Brazilians. With regard to indebtedness, Brazilians again achieved worrying results, with a high level of indebtedness and low guarantee of their own capital, unlike the English, which showed satisfactory results. The data also show the high fundraising by English clubs, reinforcing the appreciation for elite football that they play. For Brazilians, clubs are improving over time, improving their financial management, albeit slowly. Before that, analyzing the individual effects of sports performance and the control variables, it was possible to identify that the control variables are capable of affecting the financial behavior of Brazilian and English clubs. Thus, based on the results achieved, it can be concluded that there was a negative relationship between sports performance and financial performance, both for Brazilian and British clubs